2014
DOI: 10.2478/ppb-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metacognitive self on confirmation bias revealed in relation to community and competence

Abstract: The main goal of our study was to investigate the role of insight into one’s own biases (metacognitive self) in the process of hypothesis validation in accordance to the two fundamental social perception domains (community and competence) on the example of confirmation bias. The study was conducted on a group of 593 participants with the use of a confirmation bias procedure, a free recall procedure and the Metacognitive Self scale. We manipulated with the domain and the value of information given to the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Ultimately, engagement in metacognition allows learners to make more symmetrical judgements about self-knowledge and the knowledge of others (Brycz, 2014), thus contributing to the achievement of the intended collaborative-constructivist learning outcomes within a community of inquiry (Rubin & Fernandes, 2013). However, for learners to engage in this process of critical assessment and regulation of their own and others' cognition, educators must purposefully steer the process (Wittenbols, 2016).…”
Section: Cognitive Presencementioning
confidence: 99%
“…Ultimately, engagement in metacognition allows learners to make more symmetrical judgements about self-knowledge and the knowledge of others (Brycz, 2014), thus contributing to the achievement of the intended collaborative-constructivist learning outcomes within a community of inquiry (Rubin & Fernandes, 2013). However, for learners to engage in this process of critical assessment and regulation of their own and others' cognition, educators must purposefully steer the process (Wittenbols, 2016).…”
Section: Cognitive Presencementioning
confidence: 99%
“…An individual with a highly developed metacognitive-self accepts, over time, biases or psychological regularities as immanent aspects of human behavior. Thanks to a high degree of metacognitive self-insight, an individual is more persistent in the face of challenge, accepts uncontrollability (Brycz, Jurek, Pastwa-Wojciechowska, Peplińska, & Bidzan, 2014), and exhibits better self-regulatory functions (Brycz, Wyszomirska-Góra, Bar-Tal, & Wisniewski, 2014). However, there is no correlation between MSQ-24 and self-esteem (Rosenberg & Gara, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…This is why we initially believed that the more our subjects saw the rules and biases in themselves, the greater were their insight into the self (metacognitive self). Further studies revealed that there is, in fact, a positive correlation between one's score on the MCSQ-40 scale and a tendency to demonstrate biases in one's behavior (Brycz et al, 2014). The index value of metacognitive self was either the mean or the sum resulting from the assessment of all 40 regularities, calculated individually for each participant.…”
Section: The Metacognitive Self Questionnaire-40mentioning
confidence: 99%